(untitled) (Bangladesh Journal of Anatomy, 2011)
Context: Medical education is a dynamic process and is changing constantly. More and more information is being dealt with everyday. Innovations are being in introduced in teaching-learning methods and tools. As an essential part of undergraduate medical education, the teaching & learning of Developmental Anatomy and Genetics have also gone through remarkable changes in recent years. Some shifts in interest and approach as well in presentation patterns can easily be noticed in the Developmental Anatomy books through their editions. Methodological probing into the situation would bring to light the specific aspects of the issue and benefit the curriculum planners and teachers of Developmental Anatomy in bringing about necessary changes in running the undergraduate courses. Study design: A descriptive observational study involving qualitative analyses. Place and period of study: Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between January 2008 to December 2008. Materials: The ‘Preface’s of all ten editions of a commonly recommended Developmental Anatomy book (‘Langman’s Medical Embryology’). Methods: The ‘Preface’s were analysed qualitatively to identify the information and explanations provided and comments made by their author/editor on the approaches taken and the means applied in the books in selecting and presenting topics, text and illustrations. The observations were organised into specific ‘theme’s. Results: Twelve ‘theme’s could be identified from the analyses of the ‘Preface’s of all ten editions of a commonly recommended Developmental Anatomy book (Langman’s Medical Embryology). These include special emphasis in the books on the maintenance of conciseness of the textbooks, on incorporation of new information, on the importance of genetics including molecular regulation and also on the clinical aspects of Developmental Anatomy and Genetics. Addition and improvement regarding illustrations are also evolved remarkably. Conclusion: Incorporating the findings of the present study with the modern ideas and trends in teaching and assessment in Developmental Anatomy and Genetics in the renowned universities of the world, as evident from the available literature, suggestions could be formulated on improving the methods of teaching and assessment in Developmental Anatomy and Genetics in Bangladesh. Key words: Developmental Anatomy Book; Preface; Theme. DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8141 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 13-20